Evaluation of different diagnostic criteria of diseases manifesting the oral cavity – A review. Part-1 - Peeyush Shivhare; Ashish Gupta; Monu Yadav; Arvinda Konidena; Lata Shankarnarayan (Journal of Oral Biology and Craniofacial Research)
There are many disorders affecting the oral cavity, which can cause difficulty in diagnosis for an oral physician. A criterion is defined as ‘a principle or standard by which something may be judged or decided’. Several criteria have been given by different authors or committee, which further aids in diagnosis of certain disease. This article encompasses a collection and analysis of all the criteria of diseases affecting the oral cavity, which will be beneficial for an oral physician in their routine clinics.